Jump into hopscotch: A game-based approach in enhancing students’ proficiency in triangle congruence - Joylie Mae E Payot; Netchie Jane Tandog; Orville J Jr. Evardo (Davao Research Journal, 2025)
Triangle congruence postulates is a crucial concept in Geometry. The integration of games into mathematics education is a significant development that can enhance student engagement and understanding. This research investigates the effectiveness of Jump into Hopscotch, a game-based approach, in enhancing students’ proficiency in triangle congruence postulates. The study, employing a quasi-experimental research design, aims to determine the difference in students' proficiency between gamified and non-gamified learning instruction. A total of 61 grade 8 students from two heterogeneous sections in a public junior high school in the province of Davao de Oro, Philippines participated in the study.  Results from a 30-item pre-test showed that both groups were comparable with low proficiency. After the intervention, the post-test result suggests a highly significant difference in the students’ proficiency in triangle congruence postulates between the experimental and control groups, with the experimental group obtaining higher scores than the control group. The finding suggests that implementing a game-based approach, specifically Jump into Hopscotch, effectively enhances the students’ proficiency in triangle congruence postulates. This study underscores the significance of integrating a game-based approach in learning, especially in mathematics, a subject often perceived as difficult and feared, to inform educators and researchers in the field of mathematics education.